The relationship between working capital management and profitability of listed manufacturing companies in Sri Lanka - Anandasayanan, S.; Raveendran, T.; Raveeswaran, M. (University of Sri Jeyawardenapura, 2012)
Working capital management is important part in firm financial management decision. An optimal working capital management is expected to contribute positively to the creation of firm value. To reach optimal working capital management firm manager should control the tradeoff between profitability and liquidity accurately. The objective of this study is to investigate the relationship of corporate profitability and working capital management. We used a sample of 30 Manufacturing companies listed in the Colombo Stock Exchange (CSE) for the period of 2003- 2007. The dependent variable, Return on total assets is used as a measure of profitability and the relationship between working capital management and corporate profitability is investigated using panel data analysis. The results of this research showed that there is statistical significance between profitability and the cash conversion cycle. Moreover managers can create profits for their companies by handling correctly the cash conversion cycle and keeping each different component (accounts receivables, accounts payables, inventory) to an optimum level.
Keywords: Corporate Profitability; Working Capital Management; Cash Conversion Cycle; Return on Total assets